Factors Related to Caring of Pediatric Nurses in Tertiary Hospitals - Bangtit, Rattanaporn; Jintrawet, Usanee; Sripusanapan, Acharaporn (Nursing Journal CMU, 2022)
Caring by pediatric nurses involves cooperation among nurses, pediatric patients, and families of pediatric patients receiving holistic care. The objective of this correlational descriptive research study was to examine caring of pediatric nurses and the relationship of emotional stability and organizational climate to caring of pediatric nurses. Watson’s concept of caring (1988) and a literature review were used as the conceptual framework in this study. The samples, selected by purposive sampling, comprised 98 registered nurses in pediatric wards of two tertiary hospitals in northern Thailand. The research instruments included the Emotional Stability Questionnaire, the Organizational Climate Questionnaire, and the Caring Behavior of Pediatric Nurses Questionnaire. Data were analyzed using descriptive statistics and Spearman’s rank correlation coefficient. The results were as follows: The total mean scores of caring of pediatric nurses were at a high level (= 102.36, SD = 12.09). In terms of each individual dimension, it was found that the mean scores of 9 out of 10 dimensions were at a high level with the highest being the 8th dimension: provision for a supportive, protective, and corrective mental, physical, sociocultural, and spiritual environment (= 17.41, SD = 2.37). Mean scores in the tenth dimension, allowance for existential-phenomenological forces, were at a moderate level (= 1.91, SD = 0.70). Emotional stability showed a statistically significant positive correlation at a high level with the caring of pediatric nurses (rs = .694, p < .05). Organizational climate had a statistically significant positive correlation at a high level with the caring of pediatric nurses (rs = .673, p < .05). The results of this study provide preliminary information about factors related to caring of pediatric nurses. Emotional stability and a positive organizational climate should be promoted among pediatric nurses to increase caring in holistically serving the needs of pediatric patients and families.